Recent advances in energy harvesting technologies - Rajput, Shailendra; Sharma, Abhishek; Jately, Vibhu; Ram, Mangey (River Publishers series in energy sustainability and efficiency, 2023)
This book discusses the application of artificial intelligence (AI) for energy harvesting.